A Candidate Ac3-S-LPS Vaccine Against S. flexneri 1b, 2a, 3a, 6, and Y Activates Long-Lived Systemic and Mucosal Immune Responses in Healthy Volunteers: Results of an Open-Label, Randomized 2 Clinical Trial - Vladimir A. Ledov; Victor V. Romanenko; Marina E. Golovina; Biana I. Alkhazova; Alexander L. Kovalchuk; Petr G. Aparin (Vaccines)
Objectives: Determination of reactogenicity and immunogenicity of a pentavalent candidate vaccine against S. flexneri 1b, 2a, 3a, 6, and Y (PLVF). Methods: The study involved 80 healthy adult volunteers aged 18–55 years. Groups were subcutaneously immunized twice at a 30-day interval with 62.5 μg/0.5 mL or 125 μg/0.5 mL of the vaccine. Results: During the entire 8-month period of post-vaccination observation, the vaccine was well tolerated, with no local or systemic reactions detected objectively. The results of laboratory studies demonstrated no effect on the main indicators of hemogram, biochemical blood test, or urinalysis. IgA, IgG, and IgM levels against LPS S. flexneri 1b, 2a, 3a, 6, and Y were examined before vaccination, a month after each vaccination, and 6 months after booster vaccination. One month after vaccination, IgA and IgG seroconversions were observed in 67.5–82.5% (depending on serotype) and 60–77.5% of volunteers, respectively. Booster immunization did not have a significant effect on vaccine immunogenicity. In two separate groups of 15 and 9 volunteers for mucosal sIgA, IgA, and IgG titer determination after immunization with a 125 μg vaccine dose, paired stool, and saliva samples were taken before and one month after vaccination. In 26.7–40% of volunteers, there was a 2-fold and higher increase in sIgA titer for the studied serotypes in the feces and in 66.7–88.9% in saliva. IgA and IgG 2-fold conversion rates were 26.7–53.3% and 33.3–46.7% in the feces, 33.3–77.9%, and 66.7–77.8% in saliva, respectively. Conclusions: the tolerability of PLVF and the pronounced humoral immune response allow us to proceed to the phase 3 clinical trial stage.